Molecular assessment of oyster microbiomes and viromes reveals their potential as pathogen and ecological sentinels - Walker, Jordan R.; Bente, Dennis A.; Burch, Megan T.; Cerqueira, Filipe M.; Ren, Ping; Labonté, Jessica M. (One health, 2025)
Oyster aquaculture world-wide is a booming industry that can provide many benefits to coastal habitats, including economic, ecosystem-level, and cultural benefits. Oysters present several risks for human consumption, including transmission of parasites, and bacterial and viral pathogens. Oyster microbiomes are well-defined, but their connection to the incidence of pathogens, humans or others, is unclear. Furthermore, viruses associated with oysters are largely unknown, and their connection to humans, animals, and ecosystem health has not been explored. Here, we employed a One Health framework and modern molecular techniques, including 16S rRNA amplicon and metagenomic sequencing, to identify links between changes in the microbial and viral communities associated with oysters and the incidence of pathogens detected in oyster tissues and their surrounding environments. In addition, we adapted the BioFire® FilmArray®, commonly used in hospitals, to determine the presence of human pathogens within the sampled oysters. We detected known human pathogens in 50 % of the oysters tested. Within the genomic datasets, we noted that pathogens of humans, animals, and plants in oysters were shared with the nearby water and sediments, suggesting a sink–source dynamic between the oysters and their surroundings. 16S rRNA gene analysis revealed that while oysters share common microbial constituents with their surrounding environments, they enrich for certain bacteria such as Mycoplasmatales, Fusobacteriales, and Spirochaetales. On the contrary, we found that oyster viromes harbored the same viruses in near equal relative abundances as their surrounding environments. Our results show how oysters could be used not only to determine the risk of human pathogens within coastal estuaries but also how oyster viruses could be used as ecosystem-level sentinels.